Dual application of synthesized SnO2 nanoparticles in ion chromatography for sensitive fluorescence determination of ketoprofen in human serum, urine, and canal water samples. (2nd August 2017) - Muhammad, Nadeem; Li, Weixia; Subhani, Qamar; Wang, Fenglian; Zhao, Yong-Gang; Zhu, Yan
Abstract : Systematic layout of dual application of SnO2 NPs in ion chromatography for selective determination of non-fluorescent KP in complex samples. Abstract : The aim of this novel study was to introduce a cheap, simple, sensitive, and green methodology involving the dual application of synthesized porous SnO2 nanoparticles (NPs) for selective conversion of non-fluorescent ketoprofen (KP) into a highly fluorescent species and as a sorbent in a μ-sample preparation method for extraction of KP from the three complex human serum, urine, and canal water samples. The clean separation and sensitive fluorescence determination of KP from these complex samples were carried out by coupling an ion chromatograph with a fluorescence detector (IC-FLD). The sorbent was prepared by a simple chemical precipitation method in water and characterized via various techniques. The porous SnO2 NPs, in addition to their role in the selective conversion of KP into a highly fluorescent species, also act as an effective sorbent for the selective degradation and elimination of polar organics, inorganic matrices, and heavy metals in complex samples. The optimized analytical method exhibited satisfactory linearity for ketoprofen in the concentration range of 0.2–1.5 mg kg −1 with a correlation coefficient ( r 2 ) of 0.997. The limit of detection (LOD) and quantification (LOQ) in human serum, urine, and canal water samples were 0.1 μg kg −1, 0.5 μg kg −1, and 0.39 μg kg −1 and 1.3 μg kg −1, 0.3 μg kg −1, and 1.7 μg kg −1, respectively. The method also showed good intra-day and inter-day precisions at the two concentration levels of 0.5 mg kg −1 and 1.3 mg kg −1 in complex samples with the relative standard deviations (RSDs) less than 16.3% ( n = 5), and satisfactory recoveries were retrieved in the range of 85.1–101.4% with minimum or no matrix effect.